The Shepherd Boy Part 2 - Dania, Deji (Literamed Publications Nigeria Limited, 2006)
In a period when fear and despair plunge the camp of Israel into disarray,and their sovereignty as a nation is being threatened... But through divine arrangement,a relatively unknown young shepherd on a different mission to the camp could not stand the blasphemy from the braggart, goliath of Gath,the time tested warlord of the Philistines.
Keywords: Christianity; Bible Stories; Religion